How to Understand Understanding - a Tribute to Professor Torben Thrane - Jensen, Helle Dam; Nølke, Henning; Vikner, Sten; Dam, Helle Vrønning (HERMES - Journal of Language and Communication in Business, 2011)
No abstract.